Comment by Arvind Sharma - Sharma, Arvind (2000)
Comments on: JRE Focus on The 50th Anniversary of the Universal Declaration ofHuman Rights, Journal of Religious Ethics 26.2 (Fall 1998) “Rethinking Human Rights: A Review Essay on Religion, Relativism, and Other Matters” by David Little, Journal of Religious Ethics 27.1 (Spring 1999)
Keywords: Revolution; Pacifism; Just War; Islam; ethical universalism